Dynamics of Restored and Natural Oyster Reefs After a Hurricane - Martinez, Meghan J.; Palmer, Terence A.; Breaux, Natasha J.; Beseres Pollack, Jennifer (Frontiers in Ecology and Evolution, 2022)
Restoration of shellfish reefs has increased exponentially over the past two decades, due in part to increased awareness of widespread oyster habitat loss. Large-scale, acute disturbances such as hurricanes have the potential to influence restoration outcomes, but because storm occurrence is unpredictable with respect to restoration timelines, the responses of restored habitats are not well understood. We quantified the ecological dynamics of a newly constructed Crassostrea virginica oyster reef and nearby reference reef in a Texas estuary immediately after Hurricane Harvey, a major category 4 storm. Biophysical structure (e.g., oyster density, shell height, sediment grain size), and community composition (abundance of reef-associated epifauna, and nearby infauna) were measured for 18 months. A sharp decrease in salinity and temporary deposition of fine sediments within the first three months corresponded with increases in oyster and epifaunal recruitment on the restored reef, although densities were generally below those measured on restored reefs without hurricanes. Criteria for oyster reef restoration success were met within 12-18 months post-storm. Infaunal densities decreased but returned to pre-storm densities within two months, but bivalves were delayed, returning to pre-storm levels after nine months. A lack of historical baseline data on the newly restored reef limited our ability to assess the magnitude of reef recovery to pre-disturbance levels or separate the direct effects of the hurricane from the dynamics of early recruitment and growth. Results provide important information about restored and natural oyster reef dynamics after large-scale disturbance and can help inform effective management and conservation measures.